2015
DOI: 10.1152/ajpheart.00272.2015
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of cardiac tissue to bisphenol a: alterations in ventricular pressure and contractility

Abstract: Biomonitoring studies have indicated that humans are routinely exposed to bisphenol A (BPA), a chemical that is commonly used in the production of polycarbonate plastics and epoxy resins. Epidemiological studies have shown that BPA exposure in humans is associated with cardiovascular disease; however, the direct effects of BPA on cardiac physiology are largely unknown. Previously, we have shown that BPA exposure slows atrioventricular electrical conduction, decreases epicardial conduction velocity, and prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…These analyses are a part of a larger integrated multi-investigator effort performed in parallel with the comprehensive GLP-compliant 2-year CLARITY-BPA chronic exposure study investigating the toxicity of BPA (21, 24). The premise for analysis of these cardiac endpoints was derived from accumulating evidence indicating that the heart is a target for the effects of the endocrine disrupting chemical BPA (1619, 37). While the heart of both males and females express estrogen receptors (38), the impacts of ER activation by estradiol and the disruptive actions of BPA in the heart are sex specifically regulated and often differ in males and females (12, 13, 1719).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses are a part of a larger integrated multi-investigator effort performed in parallel with the comprehensive GLP-compliant 2-year CLARITY-BPA chronic exposure study investigating the toxicity of BPA (21, 24). The premise for analysis of these cardiac endpoints was derived from accumulating evidence indicating that the heart is a target for the effects of the endocrine disrupting chemical BPA (1619, 37). While the heart of both males and females express estrogen receptors (38), the impacts of ER activation by estradiol and the disruptive actions of BPA in the heart are sex specifically regulated and often differ in males and females (12, 13, 1719).…”
Section: Discussionmentioning
confidence: 99%
“…These estrogen-like effects of BPA increased arrhythmia frequencies in response to β-adrenergic stress in isolated hearts from female rats and mice, but not those of males (13). Additional in vitro studies have also demonstrated that acute exposures to high concentrations of BPA could decrease the rate and force of contractility and cardiac conduction velocity in hearts from female rats (14, 15) and to a lesser extent in the male heart (16). In vivo studies involving analysis of large numbers of male and female CD-1 or C57Bl/6n mice exposed throughout life to a wide range of BPA doses have also identified a number of sex and strain specific exposure-related effects (1719).…”
Section: Introductionmentioning
confidence: 98%
“…Isovolumic LVDP was measured by inserting a latex balloon (size 5) into the LV using established techniques [17, 41]. The balloon was attached to a pressure transducer and the diastolic LV pressure was set to 10 mmHg using a spindle syringe.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal rat ventricular myocytes were isolated and plated from a heterogeneous population of hearts, as previously described [41, 42]. Intracellular Ca 2+ transients were imaged using Fluo-4 and confocal fluorescence microscopy [42].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have established the role of bisphenol in cardiovascular diseases, including myocardial infarction, cardiomyopathy, and hypertensive heart disease [105][106][107][108][109]. A survey conducted in the United States shows the correlation between urinary BPA levels and increased prevalence of heart disease [84].…”
Section: Cardiovascular Toxicitymentioning
confidence: 99%